RECEPTION ANALYSIS OF QUIZZIZ-BASED GAMIFICATION IN ISLAMIC RELIGIOUS EDUCATION AT VOCATIONAL HIGH SCHOOLS - Indry Ayu Yuliana; Dini Siamika Tito Prayogi; Agus Miftahorrahman (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2025)
This study aimed to explore how students at Vocational High School interpret the use of Quizizz in Islamic Religious Education (IRE) classes and to identify the factors influencing their reception. Utilizing a descriptive qualitative approach and Stuart Hall’s reception theory, this research positions teachers as encoders, students as decoders, and Quizizz as the medium. Data were collected through in-depth interviews, participant observations, and documentation involving three students and two IRE teachers. The findings revealed that most students adopted a dominant-hegemonic position, perceiving Quizizz as engaging and motivational, while a minority displayed a negotiated position, appreciating the gamification format but expressing concerns about the depth of spiritual content. Factors influencing reception include students’ religious background, prior learning experience, digital literacy, classroom dynamics, and the interactive design of Quizizz. The study highlights the importance of teacher strategies in balancing entertainment and educational substance. This research contributed academically by applying Hall’s reception model to Islamic education and practically by informing teachers and policymakers about the pedagogical potential of gamification. Despite its depth, the study's limitations lied in its small sample size and the absence of quantitative learning outcome measurements. Future research could adopt a mixed-methods approach and involve broader educational contexts to enhance generalizability and provide a more comprehensive understanding of gamification in religious education.